2022
DOI: 10.7759/cureus.22064
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Survival Outcomes of Colorectal Cancer Patients After Surgical Resection

Abstract: Introduction: Colorectal cancer is one of the most common cancers in the United States. Significant disparities exist among racial and ethnic minorities diagnosed with colorectal cancer compared to non-Hispanic Whites. However, understanding of survival outcomes following curative surgical resection in this population is limited.Objective: To evaluate the association between race and colorectal cancer-specific mortality in patients who were treated with major surgical resection of the colon.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…We found that the 5‐year CRC survival rates were lower among Black patients in comparison to White patients (65.4% vs. 69.9%). This is consistent with prior literature that reported overall 5‐year CRC survival rates for Black adults have consistently been below that of White adults, with Black adults' overall survival rates at 61% and White adults' survival rates at 67% during 2000–2016 in the United States 3 . Further, we found that Black patients living in low‐education (59.4% vs. 67.3%) regions appeared to have lower 5‐year survival rates compared to those not living in low‐education regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the 5‐year CRC survival rates were lower among Black patients in comparison to White patients (65.4% vs. 69.9%). This is consistent with prior literature that reported overall 5‐year CRC survival rates for Black adults have consistently been below that of White adults, with Black adults' overall survival rates at 61% and White adults' survival rates at 67% during 2000–2016 in the United States 3 . Further, we found that Black patients living in low‐education (59.4% vs. 67.3%) regions appeared to have lower 5‐year survival rates compared to those not living in low‐education regions.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with prior literature that reported overall 5-year CRC survival rates for Black adults have consistently been below that of White adults, with Black adults' overall survival rates at 61% and White adults' survival rates at 67% during 2000-2016 in the United States. 3 Further, we found that Black patients living in low-education (59.4% vs. 67.3%) regions appeared to have lower 5-year survival rates compared to those not living in low-education regions. Compared with findings from other studies, the 5-year survival rate was 72.4% for the lowest SES quintile compared to 78.9% in the highest SES quintile for CRC patients, 23 which is in line with our findings.…”
Section: Discussionmentioning
confidence: 58%
“…[23][24][25][26][27][28] Historically, if studies examining LARC have incorporated SDOH, it has been to a limited extent. 19,20,24,[29][30][31][32][33][34][35] As an illustration, a recent study of patients with colorectal cancer undergoing surgery 36 demonstrated decreased 1-and 5-year survival for Asian, Hispanic, non-Hispanic Black, and Pacific Islander patient populations compared with White patients. This disparity persisted after adjustment for multiple demographic variables, including insurance status and marital status, with Hispanic patients exhibiting the worst survival decrement.…”
Section: Introductionmentioning
confidence: 99%
“…This disparity persisted after adjustment for multiple demographic variables, including insurance status and marital status, with Hispanic patients exhibiting the worst survival decrement. 36 However, multiple additional factors are evidently at work. Herein, we have undertaken an analysis using a focused inventory of SDOH in addition to prognostically relevant demographic, clinical, and pathologic data within a contemporary National Cancer Database (NCDB) cohort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation